Strategies to achieving deep decarbonisation in power generation: A review - Abdullah Alotaiq (Journal of Economy and Technology)
Transitioning to low-carbon power generation is crucial for combatting climate change and achieving sustainability goals. This review delves into the literature on deep decarbonisation strategies within the power sector, examining the economic costs and associated challenges. Methodologically, over 2000 studies were screened, with 30 systematically reviewed to extract insights into transitional strategies and cost implications. The literature underscores the pivotal role of power generation in reducing greenhouse gas emissions, emphasising the urgency of substantial emissions reductions by 2050. While faster transitions to low-carbon power may incur higher costs initially, delaying the transition could lead to significant economic and environmental consequences. Two primary strategies emerge, one centred on renewable energy sources and another incorporating diverse low-carbon technologies. However, hybrid approaches that combine various technologies are highlighted as optimal for minimising costs and enhancing flexibility. In conclusion, this study highlights the importance of identifying cost-effective pathways for power sector decarbonisation, with implications for future research and policymaking to address the challenges effectively.